Implementasi Nilai-Nilai Pendidikan Karakter Peduli Lingkungan Anak Usia Dini Pada Tayo The Little Bus Movie - Rahmawati, Siti; Muthohar, Sofa; Fatmawati, Nilal Muna (Jurnal Ilmiah Global Education, 2025)
The purpose of this study is to analyze in depth the content of character education values, especially concern for the environment contained in the animated cartoon series "Tayo The Little Bus" and its relevance as a learning medium for early childhood. This research is a library research with a qualitative descriptive method that applies content analysis. The research data comes from five episodes of the animated cartoon "Tayo The Little Bus" which were specifically selected to raise the theme of cleanliness and the environment. Data collection was carried out through documentation techniques with observation methods of listening and taking notes on the elements of analysis in the form of dialogue, narration, scene engineering, and character actions contained in the five episodes. The collected data were analyzed and interpreted by referring to the theory of cognitive and moral development of early childhood and the basis of character education. The results of the analysis show that in terms of cognitive aspects, this animation successfully presents the concept of introducing waste and environmental cleanliness responsibilities into concrete images through character visualization in its five episodes based on children's thinking stages. The Tayo The Little Bus cartoon animation presents a strong behavioral model through musical scenes in the episodes "Cleaning Song" and "I Like Clean Mountains" which are arranged to stimulate positive psychomotor skills in children, and the form of the story in these episodes consistently builds an understanding of the real impact of actions to protect and from actions to ignore the environment. In conclusion, as a learning through media, "Tayo The Little Bus" has strong feasibility to be used as a supporting medium in environmental care character education at the Early Childhood Education level.